Shapes : britannica discovery library - Taylor, Joseph (Encyclopaedia Britannica, Inc. Chicago, 2005)
This entry provides an insightful overview of shapes, examining their mathematical properties and aesthetic significance in art and nature. It highlights how shapes are fundamental to understanding both geometry and the visual world around us.